In vitro and in vivo approaches for identifying the role of aryl hydrocarbon receptor in the development of nonalcoholic fatty liver disease. (1st February 2020) - Zhu, Xiang-Yu; Xia, Hong-Guang; Wang, Zhi-Hao; Li, Biao; Jiang, Hai-Yan; Li, Da-Lang; Jin, Rui; Jin, Yong
Graphical abstract: Highlights: AhR is a novel regulator of the development of NAFLD. CYP1A1 is not only a general surrogate marker for AhR activation but also a key enzyme for estrogen metabolism. AhR activation induces the overexpression of CYP1A1 and interferes with estrogen homeostasis. AhR activation inhibits the regulation of estrogen on hepatic steatosis, characterized by the accumulation of triglycerides. Abstract: Nonalcoholic fatty liver disease (NAFLD) is a chronic hepatic disease associated with the excessive accumulation of lipids in the liver. Premenopausal women are protected from the liver metabolic complications of obesity compared with body mass index (BMI)-matched men. This protection may be related to estrogen's ability to limit liver fat accumulation. Aryl hydrocarbon receptor (AhR), a novel regulator of NAFLD, may be an important target for regulating estrogen homeostasis. In present study, we used benzo[ a ]pyrene (BaP), a classic and potent ligand of AhR, to activate AhR pathway causes overexpression of the estrogen-metabolizing enzyme cytochrome P450 1A1 (CYP1A1) and affects the expression of important genes involved in hepatic lipid regulation. BaP induces CYP1A1 expression through AhR signaling and inhibits the protective effect of 17β-estradiol (E2) on hepatic steatosis, characterized by triglyceride accumulation, and markers of liver damage are significantly elevated. The expression of adipogenic genes involved in the hepatic lipid metabolism of sterol regulatory element-binding protein-1c (SREBP-1c) was increased compared with that in the control group. Furthermore, the mRNA and protein levels of peroxisome proliferator-activated receptor alpha (PPARα), which is involved in fatty acid oxidation, were significantly reduced. Taken together, our results revealed that the steatotic effect of AhR is likely due to overexpression of the E2 metabolic enzyme CYP1A1, which affects the estrogen signaling pathway, leading to the suppression of fatty acid oxidation, inhibition of the hepatic export of triglycerides, and an increase in peripheral fat mobilization. The results from this study may help establish AhR as a novel therapeutic and preventive target for fatty liver disease.